2013
DOI: 10.1016/j.cmet.2013.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Activation of mTORC1 in Skeletal Muscle Inhibits Constitutive and Starvation-Induced Autophagy and Causes a Severe, Late-Onset Myopathy

Abstract: Autophagy is a catabolic process that ensures homeostatic cell clearance and is deregulated in a growing number of myopathological conditions. Although FoxO3 was shown to promote the expression of autophagy-related genes in skeletal muscle, the mechanisms triggering autophagy are unclear. We show that TSC1-deficient mice (TSCmKO), characterized by sustained activation of mTORC1, develop a late-onset myopathy related to impaired autophagy. In young TSCmKO mice, constitutive and starvation-induced autophagy is b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
281
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 231 publications
(310 citation statements)
references
References 35 publications
27
281
2
Order By: Relevance
“…Mutations in lipin 1 PAP activity would be predicted to increase the cellular PA concentration, which may be toxic and/or activate inflammatory MAPK signaling cascades (Nadra et al 2008). PA also activates mTORC1 kinase (Sun and Chen 2008;Mitra et al 2013), which has been linked to development of muscle injury and myopathy (Castets et al 2013) Leu635Pro (*P < 0.05, t-test). (c) Coomassie stain and PAP activity of purified recombinant WT lipin 1, p.Leu635Pro, and p.Arg725His.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in lipin 1 PAP activity would be predicted to increase the cellular PA concentration, which may be toxic and/or activate inflammatory MAPK signaling cascades (Nadra et al 2008). PA also activates mTORC1 kinase (Sun and Chen 2008;Mitra et al 2013), which has been linked to development of muscle injury and myopathy (Castets et al 2013) Leu635Pro (*P < 0.05, t-test). (c) Coomassie stain and PAP activity of purified recombinant WT lipin 1, p.Leu635Pro, and p.Arg725His.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, under stress conditions such as energy depletion resulting in an increased AMP to ATP ratio, the protein kinase AMPK is activated through phosphorylation by upstream kinases, such as LKB1 (Hardie, Ross, & Hawley, 2012), and phosphorylates TSC2 to enhance its GAP activity (Inoki, Zhu, & Guan, 2003). Thus, since the TSC complex integrates multiple upstream signals to negatively regulate a key step in mTORC1 activation, its disruption causes constitutive mTORC1 activation (Byles et al, 2013; Castets et al, 2013; Kwiatkowski et al, 2002). …”
Section: Mtor and Metabolismmentioning
confidence: 99%
“…10,11 It has thus been shown that intraperitoneal (IP) injection of leupeptin triggers significant accumulation of LC3-II in liver as early as 30 to 60 min after the treatment, 10 whereas most of the studies focusing on skeletal muscle treated mice for no less than 2 d (i.e., a daily injection from 2 to 10 d). 9,[11][12][13] As a consequence, the prolonged use of these drugs could induce collateral effects that might directly or indirectly affect autophagy. For instance, Ju et al report that both LC3-I and LC3-II levels increase in skeletal muscle of mice treated with colchicine beyond 5 d, suggesting that the long-period treatments induce autophagic flux blockage but also enhance autophagy.…”
Section: Introductionmentioning
confidence: 99%